2021
DOI: 10.1177/0020720920983999
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Individualized learning evaluation model based on hybrid teaching

Abstract: A hybrid teaching model which combines traditional classroom with online learning emerges as the times require. Hybrid teaching uses information technology to reorganize the various elements of teaching so that traditional teaching and new technology application can complement each other, and gradually get the attention and attention of teachers and students. This paper compares the mixed teaching with the traditional single teaching, and discusses the role of the mixed teaching mode in promoting the personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…For instance, game-based learning, blended learning, mind mapping, and scales assessing the learning process were included. Studies have shown that gamified learning, classroom games, and blended learning are innovations that can improve students’ learning and support their personalized evaluation (Hasan et al, 2017; Radley et al, 2016; Wu et al, 2023). Moreover, many evaluation methods, such as performance evaluation and mind mapping, are student-centered and can be used to monitor students’ learning processes and performance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, game-based learning, blended learning, mind mapping, and scales assessing the learning process were included. Studies have shown that gamified learning, classroom games, and blended learning are innovations that can improve students’ learning and support their personalized evaluation (Hasan et al, 2017; Radley et al, 2016; Wu et al, 2023). Moreover, many evaluation methods, such as performance evaluation and mind mapping, are student-centered and can be used to monitor students’ learning processes and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Blended teaching is compared with traditional single teaching to explore the promotion effect of the blended teaching model on personalized learning of basic courses and the impact on the quality of learning. The results demonstrate that blended instruction facilitates students' self-directed learning compared to a single instructional approach [15]. Abdullah, A et al created a blended instructional model and instructional materials for a linguistics course to enhance students' language knowledge, theory and skills.…”
Section: Introductionmentioning
confidence: 92%
“…The traditional teaching mode can no longer meet the needs of modern education and teaching for talent development ( Wen, 2022 ), but in higher education teaching practice, the traditional teaching mode centered on a classroom, teacher, and textbook is still more often used for teaching ( González Velasco et al, 2021 ). There are problems such as the traditional teaching concept of taking teachers as the main body of teaching ( Yang et al, 2021 ), lack of teaching resources ( Niu et al, 2019 ), and single teaching method ( Wu et al, 2021 ). Current higher education needs to explore new teaching models with the help of modern information technology, to promote innovation and change in education informatization, and further promote the realization of education modernization.…”
Section: Introductionmentioning
confidence: 99%